Week 8 Assignment

# Week 8 Assignment - Week 8 Assignment Section 5.4 2 86 48...

This preview shows pages 1–6. Sign up to view the full content.

Week 8 Assignment Section 5.4 2. √8√6 √48 √16√3 √4√3 7. (-3√3)(-4√8) 12√24 12√4√6 12(2)√6 24√6 11. (2 3 √4)(6 3 √2) 12 3 √8 12(2) 24 15. √2(√3 + √5) √6 + √10 17. 3√5(2√2 - √7) 6√10 - 3√35 21. -4√5(2√5 + 4√12) -8√25 - 16√60 -8(5) - 16√4√15 -8(5) - 16(2)√15 -40 - 32√15 23. 3√x(5√2 + √y) 15√2x + 3 √xy 25. √xy(5√xy - 6√x) 5√x 2 y 2 - 6√x 2 y

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
31. (√3 + 4)(√3 - 7) √9 - 7√3 + 4√3 - 28 3 - 3√3 - 28 -25 - 3√3 35. (3√5 - 2√3)(2√7 + √2) FOIL 6√35 + 3√10 - 4√21 - 2√6 38. (5√2 - 4√6)(2√8 + √6) 10√16 + 5√12 - 8√48 - 4√36 (8√3√2√2 was reduced from 8√6√8) 10√4√4 + 5√2√3 - 8√3√2√2 - 4√6√6 (5√2√3 was reduced from 5√4√3) 10(4) + √10√3 - 32√3 - 4(6) 40 + (-24) + 10√3 - 32√3 10√3 - 32√3 = (10-32)√3 40 - 24 = 16 10 - 32 = -22 16 - 22√3 41. (3√2 - 5√3)(6√2 - 7√3) 18√4 - 21√6 - 30√6 + 35√9 18√2√2 - 21√6 - 30√6 + 35√3√3 18(2) - 21√6 - 30√6 + 35(3) 36 - 51√6 + 105 141 - 51√6 43. (√6 + 4)(√6 - 4) √36 - 4√6 + 4√6 - 16 √6 - 16 -10 47. (√2x + √3y)(√2x - √3y) 4x 2 + √6xy + √6xy - √9y 2 2x - 3y 49. 2 3 √3(5√4 + 3 √6) 10 3 √12 + 2 3 √18
51. 3 3 √4(2 3 √2 - 6 3 √4) 6 3 √8 - 18 3 √16 6(2) - 18 3 √16 12 - 18(2) 3 √2 12 - 36 3 √2 53. 2 √7 + 1 2 * (√7 - 1) (√7 + 1) (√7 - 1) 2(√7 - 1) = 2(√7 - 1) √49 - 1 7 - 1 2(√7 - 1) = √7 - 1 6 3 59. √2 = √2 * (√10 + √3) = √10 - √3 (√10 - √3) (√10 + √3) √3(2√5 - 4) = 2√15 - 4√3 = √100 - √9 10 - 3 √4√5 + √6 = 2√5 + √6 7 7 65. √6 = 3√2 + 2√3 √6 * (3√2 - 2√3) = (3√2 + 2√3) (3√2 - 2√3) √6(3√2 - 2√3) = 3√12 - 2√18 = 9√4 - 4√9 9(2) - 4(3) 3√4√3 - 2√9√2 = 6√3 - 6√2 = 18 - 12 6 6(√3 - √2) = √3 - √2 6

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
67. 2 = √x + 4 2 * (√x - 4) = √x + 4 (√x - 4) 2(√x - 4) = 2√x - 8 = √x 2 - 25 x - 25 x + 5√x x - 25 69. √2 = √x * (√x + 5) = √x + 5 (√x - 5) (√x + 5) √x(√x + 5) = √x 2 + 5√x = √x 2 - 25 x - 25 x + 5√x x - 25 73. √x = √x + 2√y √x * (√x - 2√y) = (√x + 2√y) (√x - 2√y) √x 2 - 2√xy = x - 2√xy √x 2 - 4√y 2 3 x - 4y Section 5.5 1. √5x = 10 (√5x) 2 = 10 2 5x = 100 x = 20 √5(20) = 10 √100 = 10 10 = 10 20
5. 2√n = 5 √n = 5 2 (√n) 2 = (5 ) 2 2 n = 25 4 2√25 = 5 4 2(5 ) = 5

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

## This note was uploaded on 04/19/2011 for the course MATH 112 taught by Professor . during the Fall '10 term at Mountain State.

### Page1 / 20

Week 8 Assignment - Week 8 Assignment Section 5.4 2 86 48...

This preview shows document pages 1 - 6. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online